Validity and Practicality of Developing Heyzine Digital Interactive Flipbook Media in Teaching Pancasila Value Elements in Grade IV Elementary School - Anastasia, Mawarni; Reinita, Reinita; Anita, Yesi; Mansurdin, Mansurdin (Journal of Educational Sciences, 2025)
This study aims to develop and evaluate the validity and practicality of an interactive digital flipbook-based learning media for teaching Pancasila Education in fourth-grade elementary school students. The research employed a Research and Development (R&D) design using the ADDIE model. Media validity was assessed by a subject matter expert (94.6%), a language expert (89%), and a media expert (91.25%), resulting in an average score of 91.63%, categorized as highly valid. Practicality testing was conducted at five elementary schools: SDN 11 Kampung Jua, SDN 03 Lubuk Begalung, SDN 10 Lubuk Begalung, SDN 27 Kampung Jua, and SDN 07 Pulau Air. Teacher responses ranged from 87.50% to 95.83%, while student responses ranged from 94.16% to 98.11%, all falling into the highly practical category. In addition, the effectiveness test showed an average N-Gain score of 0.63, categorized as moderate. These findings indicate that the digital flipbook media is valid, highly practical, and reasonably effective for supporting Pancasila Education learning in elementary schools.